The construction of a modified sampling scheme by variables inspection based on the one-sided capability index. (August 2018) - Lee, Amy H.I.; Wu, Chien-Wei; Wang, Zih-Huei
Highlights: The paper develops a modified sampling plan that considers preceding lot information. The OC curve of the proposed plan is derived using the exact sampling distribution. The efficiency of the proposed and existing plans are examined and compared. The proposed plan can provide the desired protections with less sampling. Tables of plan parameters are provided and an example is studied for illustration. Abstract: Several process capability indices have been applied to develop variables single sampling plans (SSPs) and repetitive group sampling plans (RGSPs) for numerical measurements of quality characteristics. Both types of plans are simple to administer and easy to implement, but neither of them considers the available information of previous collected samples. In this study, we develop a modified variables repetitive group sampling plan (Modified-VRGSP) to overcome the disadvantages of the SSP and the RGSP by considering the quality history of preceding lots based on the one-sided capability index. By minimizing the average sample number while satisfying the quality levels demanded by both the producer and the consumer, the plan parameters can be obtained for product acceptance determination. The advantages of the proposed plan over existing variables sampling plans are presented.